2016
DOI: 10.1111/trf.13657
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Jehovah's Witnesses after adult cardiac surgery: systematic review and meta‐analysis of comparative studies

Abstract: JWs undergoing adult cardiac surgery have a nonsignificant trend toward better early outcome than controls receiving or not blood transfusions. The suboptimal quality of available studies prevents conclusive results on the possible benefits of a transfusion-free strategy in patients not refusing blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…The results of this study emphasize the significance of attempts to prevent excessive bleeding and blood transfusion also in low‐risk patients. On the basis of previous evidence, cardiac operations with minimal blood loss and no transfusion of blood products are possible to perform successfully . This requires an interdisciplinary multimodal approach to patient blood management and a meticulous surgical technique to minimize bleeding misadventures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study emphasize the significance of attempts to prevent excessive bleeding and blood transfusion also in low‐risk patients. On the basis of previous evidence, cardiac operations with minimal blood loss and no transfusion of blood products are possible to perform successfully . This requires an interdisciplinary multimodal approach to patient blood management and a meticulous surgical technique to minimize bleeding misadventures.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, preoperative correction of anemia can be considered to be of utmost importance. Recently, a meta‐analysis investigating Jehovah's Witnesses undergoing cardiac surgery and refusing transfusion of blood products showed promising results . Pooled analysis of postoperative outcomes showed that Jehovah's Witnesses (n = 564) had higher postoperative levels of Hb and significantly less postoperative blood loss (mean, 402 mL vs. 826 mL; p < 0.001) compared to controls (n = 903).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who refuse alloBT are at increased theoretical risk for increased morbidity and mortality associated with intraoperative bleeding and coagulation deficiencies. Despite the theoretical risks, published data demonstrates equal outcomes in patients who refuse alloBT and undergo coronary artery bypass graft (CABG) or CABG in combination with valve surgeries 3‐5 . When excessive bleeding occurs, minimal options exist to mitigate blood loss and morbidity in patients who refuse alloBT.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the theoretical risks, published data demonstrates equal outcomes in patients who refuse alloBT and undergo coronary artery bypass graft (CABG) or CABG in combination with valve surgeries. [3][4][5] When excessive bleeding occurs, minimal options exist to mitigate blood loss and morbidity in patients who refuse alloBT. The use of four-factor prothrombin complex concentrate (4PCC) to decrease bleeding related to coagulopathy is an alternative to alloBT and is generally acceptable among JW patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation